Racial disparities in the treatment of acute overdose in the emergency department. (2nd December 2018) - Wilder, Marcee E.; Richardson, Lynne D.; Hoffman, Robert S.; Winkel, Gary; Manini, Alex F.
Abstract: Objectives: Racial and ethnic disparities in the United States continue to exist in many disciplines of medicine, extending to care in the Emergency Department (ED). We sought to examine the relationship between patient race/ethnicity and use of either antidotal therapy or gastrointestinal decontamination for individuals presenting to the ED for acute drug overdose. Methods: We completed a secondary analysis of a prospective cohort of patients with suspected acute overdose presenting to two urban tertiary care hospitals between 2009 and 2014. Race was self-identified during ED registration. Antidote administration (primary outcome) and gastrointestinal decontamination (secondary outcome) were reviewed and verified via agreement between two board certified medical toxicologists. Associations between race and outcomes were analyzed using a logistic regression model. Results: We reviewed 3252 ED patients with acute overdose. Overall, 542 people were treated with an antidote and 234 cases were treated with activated charcoal, either single or multiple dose. Compared to Whites, Blacks and Hispanics were significantly less likely to receive any antidote. The analysis was underpowered to detect racial disparities in the administration of activated charcoal. Conclusions : Blacks and Hispanics are significantly less likely to receive any antidote when presenting to the ED for acute drug overdose. Further studies are needed to determine national prevalence of this apparent disparity in care and to fully characterize how race plays a role in management of acute overdose.